2020
DOI: 10.1007/978-3-030-61702-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Methodologies Against Money Laundering in Non-Banking Correspondents

Abstract: The activities of money laundering are a result of corruption, illegal activities, and organized crime that affect social dynamics and involved, directly and indirectly, several communities through different mechanisms to launder illegal money. In this article, we propose a machine learning approach to the analysis of suspicious activities in nonbanking correspondents, a type of financial agent that develops some financial transactions for specific banking customers. This article uses several algorithms to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It can analyze transaction data and identify unusual patterns that may indicate fraudulent activity. These algorithms can flag potentially fraudulent transactions in real-time, preventing losses and enhancing the security of financial systems (Guevara, Garcia-Bedoya, & Granados, 2020;Lokanan, 2022).…”
Section: Fraud Detectionmentioning
confidence: 99%
“…It can analyze transaction data and identify unusual patterns that may indicate fraudulent activity. These algorithms can flag potentially fraudulent transactions in real-time, preventing losses and enhancing the security of financial systems (Guevara, Garcia-Bedoya, & Granados, 2020;Lokanan, 2022).…”
Section: Fraud Detectionmentioning
confidence: 99%
“…In the AML domain, a recent research trend has demonstrated the effectiveness of the application of Isolation Forests and Support Vector Machines to the detection of money laundering patterns [20], [21].…”
Section: A Unsupervised Learningmentioning
confidence: 99%
“…As pointed out in Section III, an unsupervised method is essential to detect new anomalous patterns never seen before. We decided to use Isolation Forest [20], [21] due to its high performance in detecting outliers even if they are present in Algorithm 1 Pseudocode of Amaretto's approach: L is the set of the feedback received by the fraud analyst; U is the set of transactions; mod is the machine learning model; sup stands for supervised; unsup stands for unsupervised; strat is the selection strategy; K denotes the top-K high-level vectors in the ranking; T denotes the set of time windows. )…”
Section: Unsupervised Modulementioning
confidence: 99%
See 1 more Smart Citation